A pilot study on longitudinal change in pancreatic proton density fat fraction during a weight-loss surgery program in adults with obesity - Covarrubias, Yesenia (J Magn Reson Imaging, 2019)
BACKGROUND: Quantitative-chemical-shift-encoded (CSE)-magnetic resonance imaging (MRI) methods have been applied to the liver. The feasibility and potential utility CSE-MRI in monitoring changes in pancreatic proton density fat fraction (PDFF) have not yet been demonstrated. PURPOSE: To use quantitative-CSE-MRI to estimate pancreatic fat changes during a weight-loss program in adults with severe obesity and nonalcoholic fatty liver disease (NAFLD). To explore the relationship of reduction in pancreatic PDFF with reductions in anthropometric-indices. STUDY TYPE: Prospective/longitudinal. POPULATION: 9 adults with severe obesity and NAFLD enrolled in a weight-loss program. FIELD STRENGTH/SEQUENCE: CSE-MRI fat quantification techniques and multistation-volumetric fat/water separation techniques were performed at 3T. ASSESSMENT: PDFF-values were recorded from parametric-maps co-localized across time points. STATISTICAL TESTS: Rates of change of log-transformed variables across time were determined (linear-regression), and their significance assessed compared to no change (Wilcoxon test). Rates of change were correlated pairwise (Spearman’s correlation). RESULTS: Mean pancreatic PDFF decreased by 5.7% (range 0.7 – 17.7%) from 14.3 to 8.6%, hepatic PDFF by 11.4% (2.6 – 22.0%) from 14.8 to 3.4%, weight by 30.9 kg (17.3 – 64.2 kg) from 119.0 to 88.1 kg, BMI by 11.0 kg/m(2) (6.3 – 19.1 kg/m(2)) from 44.1 to 32.9 kg/m(2), WC by 25.2 cm (4.0 – 41.0 cm) from 133.1 to 107.9 cm, HC by 23.5 cm (4.5 – 47.0 cm) from 135.8 to 112.3 cm, VAT by 2.9 L (1.7 – 5.7 L) from 7.1 to 4.2 L, SCAT by 4.0 L (2.9 – 7.4 L) from 15.0 to 11.0 L. Log-transformed rate of change for pancreatic PDFF was moderately correlated with log-transformed rates for hepatic PDFF, VAT, SCAT, and WC (ρ = 0.5, 0.47, 0.45, and 0.48 respectively), although not statistically significant. DATA CONCLUSION: Changes in pancreatic PDFF can be estimated by quantitative-CSE-MRI in adults undergoing a WLS program. Pancreatic and hepatic PDFF, and anthropometric-indices decreased significantly.